Strategi Dalam Meningkatkan Kualitas Pendidikan Di Daerah Dan Satuan Pendidikan - Syibromilisi; Agus Alif Humaydiy; Sopidi Sopidi (TSAQAFATUNA : Jurnal Ilmu Pendidikan Islam, 2026)
The quality of education remains a central issue in human resource development and regional competitiveness. However, many regions and education units still face unequal educational quality, uneven teacher professionalism, weak school governance, and limited educational infrastructure. This article aims to analyze strategies for improving education quality at the regional and school levels through a conceptual literature review. The data were obtained from academic books, accredited national journals, selected international references, and official education policy documents published between 2012 and 2026. The literature was reviewed through thematic content analysis by classifying findings into leadership, teacher professionalism, learning process, educational technology, and stakeholder participation. The results show that education quality improvement requires integrated strategies, including strengthening instructional leadership and data-based school governance, developing continuous teacher professionalism, optimizing contextual and inclusive learning, using educational technology strategically, and strengthening community participation. The contribution of this article lies in the formulation of a contextual strategy framework that can guide local governments and education units in designing sustainable quality improvement programs.